PENERAPAN ARSITEKTUR BIOKLIMATIK PADA PUSAT PELELANGAN IKAN (PPI) DI KABUATEN LUWU UTARA - Pratama, Awal; Sutrisno, Mohammad; Abdullah, Sudarman (TIMPALAJA : Architecture Student Journals, 2026)
North Luwu Regency has significant potential in the fisheries sector, supported by its coastal area facing Bone Bay and the increasing trend of fishery production over the years. However, the lack of an adequate Fish Auction Center has led to suboptimal fish landing, auction, distribution, and marketing activities. This design aims to develop a Fish Auction Center in North Luwu Regency that is functional, comfortable, energy-efficient, and responsive to the tropical coastal climate through the application of bioclimatic architecture. The method used is a descriptive, qualitative approach with an architectural design focus, conducted through literature reviews, field surveys, site analysis, and local climate analysis. The collected data were analyzed to formulate design strategies that correspond to the needs of coastal community activities and the principles of bioclimatic architecture. The design results show that integrating natural ventilation, vegetation, rainwater management, natural lighting, and selecting materials such as laminated wood, granite tile, and reflective roofing can support thermal comfort, energy efficiency, and building sustainability. Therefore, the proposed Fish Auction Center is expected to serve as a fisheries facility that supports fishermen's economic activities while providing a building that is adaptable to the coastal environment.